THE INFLUENCE OF LISTENING TO SONG “LOOK AT THE SPEAKER” TO IMPROVE STUDENTS’ SPEAKING ABILITY AT THE GRADE VIII IN SMP NEGERI 4 PADANGSIDIMPUAN - KHAIRUNNISAH KHAIRUNNISAH (Linguistik : Jurnal Bahasa dan Sastra, 2016)
The aim of this research improve students speaking ability through listening song “Look at the Speaker” the students could improve their speaking ability especially in pronounciation the word and stressing or intonation. The students also could learn about grammar and could make the sentences from the words of song.The research was designed using qualitative method with descriptive type. This research designed by using qualitative descriptive and the instrument used the human  with recorded some activities of teaching and learning process in classroom and interviewed. The finding of this research showed that the use of songs in teaching English have influence to improve the students’ speaking and very beneficial for the studentsin order to facilitate them in learning English. Based on this finding, it is suggested that songs in teaching English can be recommended for the teacher of English.